THE INFLUENCE OF MUDHARABAH AND MUSYARAKAH INCOME TOWARDS BRI SYARIAH PROFITABILITY - Zulkarnain Karundeng (Tasharruf: Journal Economics and Business of Islam, 2017)
AbstractThis study aims to discover the influents of Mudharabah and Musyarakah income towards BRI Syariah profitability. The researcher applied the quantitative method using two variables. They are mudharabah and musyarakah (x) and profitability (y). The research samples are quarterly financial report published by BRI Syariah during 2010-2015 periods. Research data are initially exposed to a classical assumption test in order to check whether those data are compatible for hypothesis test. The classical assumption test includes normality, multicollinearity, autocorrelations and heteroscedasticity test. Based on the hypothesis test, the dependent variable which can be explained by the independent variables is 29,9 % while the rest 71,1 % are explained by other variables. The simultant test (F) shows that variable x is influenced by variable y. it is proven by a p-value that is smaller than the level of significant (0,027 < 0,05). On the other hand, musyarakah is not affected since the p-value is bigger than the level of significant (0,319 > 0.15).Keywords :Mudharabah, Musyarakah, Profitability